Cita Rasa, Harga, dan Kualitas Pelayanan sebagai Prediktor Keputusan Pembelian Konsumen: Studi Empiris Koffiekopi Jambi - Doni Inra; Jaelani Jaelani (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of taste, price, and service quality on consumer purchasing decisions at Koffiekopi Jambi, a rapidly growing local coffee shop brand in Indonesia. Given the increasingly fierce competition in the local coffee industry, it is important for business owners to understand the factors that influence consumer product choices. This study used a quantitative method, collecting data through a structured questionnaire distributed to Koffiekopi Jambi consumers. The collected data were then analyzed using multiple linear regression using SPSS version 25 to examine the relationship between variables. The analysis results show that taste and price significantly influence consumer purchasing decisions. Consistent taste and compliance with consumer preferences are the main factors influencing their decision to purchase coffee products at Koffiekopi Jambi. In addition, price is also an important factor influencing purchasing decisions, with consumers tending to choose products that offer good economic value according to their expectations. On the other hand, service quality does not have a statistically significant influence on purchasing decisions at this coffee shop. These findings align with the literature that emphasizes the importance of product attributes such as taste and price in determining consumer purchasing behavior. Although service quality did not show a significant influence in this model, this study still recommends continuing to improve service aspects as part of a better customer experience. Improving service quality can strengthen customer loyalty and provide a long-term competitive advantage. This study provides an important contribution to developing marketing strategies based on consumer preferences, particularly in the increasingly competitive coffee industry. Local coffee businesses, such as Koffiekopi Jambi, are expected to utilize these findings to develop more effective strategies to attract and retain customers.